Triaxial Tests for Soils - Valerio Salas, Oscar (2025)
This document presents a brief explanation of the shear strength theory, an overview of the main types of triaxial tests that are performed more frequently in a geotechnical laboratory and a detailed listing of the different components that make up the triaxial test equipment acquired by the LanammeUCR Geotechnical Laboratory. Finally it presents the assembly and some of the results from the execution of a UU triaxial test